History and Bathymetry of a Surge-dammed Lake - Collins, Sam G.; Clarke, Garry K.C. (ARCTIC, 1977)
A survey was made in 1974 of the small lake which had formed as a result of the surge advance of Steele Glacier, Yukon Territory, in 1965-68. Maximum lake level is controlled by a drainage channel which passes over rock near the hydrologic left margin of Steele Glacier. Since the surge advance of 1965-68 the lake has twice drained subglacially, producing minor outburst floods on Steele Creek and increasing the discharge of the Donjek River which crosses the probable route of the Alaska Highway pipeline.